TT ARIETIS: UNPRECEDENTED SWITCHING FROM NEGATIVE TO POSITIVE SUPERHUMPS - Andronov, I. L.; Antoniuk, K. A.; Apeltauer, T.; Chinarova, L. L.; Galis, R.; Hric, L.; Kolesnikov, S. V.; Niarchos, P. G.; Novak, P.; Patkos, L.; Shakhovskoy, D. N.; Shakhovskoy, N. M. (Одеські астрономічні публікації, 2017)
Results of the international observational campaign "TT Ari-98" are presented. Altogether 11 336 observations have been obtained in the "positive superhump" state during 18 runs in 6 observatories, partially in UBV, UBVR (switching filters). During one night, 1027 simultaneous UBVRI data have been obtained. No significant shifts between the times of extrema in different colors have been found. The asymmetry is 0.44±0.01 is present showing more abrupt brightness increase than a decrease. The smoothed U-B color varies from -0m.65 to - 0m. 86, whereas the B-V=0m. 03 is remarkably constant. Sometimes the maxima have larger amplitude and a sharp shape corresponding to areas with a duration of ∼ 5 minutes. One may note a significant decrease of the mean magnitude by 0m. 35 on JD 2251069. The moments of 21 maximum and 18 minima are listed. They correspond to the period for the 1997 data obtained by Skillman et al. (1998) showing no period change from one season to the next. The "test function - frequency" dependence in a double logarithmic scale has a linear trend in the range (90-370 c/d) and a very large slope 2.3-3.1 corresponding to QPOs rather than to the flickering.